2023
DOI: 10.1364/ome.476935
|View full text |Cite
|
Sign up to set email alerts
|

High energy radiation damage on silicon photonic devices: a review

Abstract: The past decade has witnessed the fast development of silicon photonics. Their superior performance compared with the electronic counterpart has made the silicon photonic device an excellent candidate for data communication, sensing, and computation. Most recently, there has been growing interest in implementing these devices in radiation harsh environments, such as nuclear reactors and outer space, where significant doses of high energy irradiation are present. Therefore, it is of paramount importance to fill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…While the space impact on electronic ICs has been studied for decades, the impact on PICs is a relatively new topic of research and there are still many open questions. 21,22 However, several studies showed promising results in terms of resilience to the space environment. For example, total ionizing dose (TID), which is one of the main radiation effects, does not introduce significant additional losses in InP, 23 Si, 24,25 SiN, 26 a-Si, 26,27 SiC, 28 and SiO 2 29 waveguides.…”
Section: Space Environment Considerationsmentioning
confidence: 99%
“…While the space impact on electronic ICs has been studied for decades, the impact on PICs is a relatively new topic of research and there are still many open questions. 21,22 However, several studies showed promising results in terms of resilience to the space environment. For example, total ionizing dose (TID), which is one of the main radiation effects, does not introduce significant additional losses in InP, 23 Si, 24,25 SiN, 26 a-Si, 26,27 SiC, 28 and SiO 2 29 waveguides.…”
Section: Space Environment Considerationsmentioning
confidence: 99%